PREDICTION OF NEW POLYNITROGEN COMPOUNDS AND ANALOGOUS AS HIGHLY ENERGETIC MATERIALS - Cubas C., R. (2009)
In the last years, the discovery of new energetic materials has accelerated due to the use of the computational quantum chemistry, identifying innovative compounds with promising energy properties. The estimate of these, as the heat of formation, density, speed of the detonation, pressure of the detonation and sensibility, allow us in a following stage, to select to the candidates potentials for laboratory synthesis. In this paper, we study the structural, electronic and spectroscopic properties of the new fullerenes nitrogen's, obtained by technical of prediction quantum. The calculations were carried out with semiempirical (PM3) and ab initio (UHF) methods.